Central Bank Money and Interest Rates: Independent Monetary Policy Tools? - Heinz-Peter Spahn (Kredit und Kapital, 2010)
Central Bank Money and Interest Rates: Independent Monetary Policy Tools? Central banks can control the macro economy by means of interest rate policies also in a cashless economy. In a monetary economy with a positive demand for base money, the quantity of money represents an additional policy tool, independent from interest rate management. This hypothesis is examined by analyzing various institutional set-ups of the money market. It is found that the two-instruments hypothesis is valid in a floor, but not in a corridor system (used by Fed and ECB). Here, central banks are led to supply base money on demand, in order to keep effective the chosen policy target rate. If strict stabilization is needed, also in an asset price bubble, monetary policy should consider a "scissors strategy" (sometimes pursued by the Bundesbank) of simultaneously increasing short-term interest rates and permitting temporarily a quantitative shortage of liquidity. (JEL E5) – – Zentralbankgeld und Zinsen: unabhängige Instrumente der Geldpolitik? Zentralbanken können über den Zins auch eine bargeldlose Wirtschaft kontrollieren. In einer Ökonomie mit positiver Geldnachfrage könnte die Variation der Geldmenge neben dem Zins ein zusätzliches Instrument darstellen. Diese Hypothese wird für verschiedene Organisationstypen des Geldmarktes geprüft. Sie gilt in einem Floor-, aber nicht in einem Korridor-System (das Fed und EZB anwenden). Im Letzteren ist das Geldangebot endogen über die Vorgabe des Leitzinses bestimmt. Wenn eine tiefgreifende monetäre Stabilisierung notwendig wird, z. B. bei einer Vermögensinflation, sollte (wie früher ansatzweise von der Bundesbank praktiziert) eine "Zangenpolitik" angewendet werden, nämlich gleichzeitig die Zinsen zu erhöhen und die Geldmenge quantitativ zu beschränken.
Keywords: E5; 330